Propensity score matched analysis of partial atrioventricular septal defect repair in infancy. Issue 12 (1st December 2017) - Buratto, Edward; Daley, Michael; Ye, Xin Tao; Radford, Dorothy J; Alphonso, Nelson; Brizard, Christian P; d'Udekem, Yves; Konstantinov, Igor E
Abstract : Objective: Partial atrioventricular septal defect (pAVSD) is usually repaired between 2 and 4 years of age with excellent results. Repair during infancy has been associated with poorer outcomes. However, most infants in reported series had heart failure or significant left atrioventricular valve (LAVV) regurgitation. The impact of surgery during infancy on outcomes remains unclear. Methods: All children at three institutions who underwent repair of pAVSD from 1975 to 2015 were included. Infants (aged <1 year) were compared with older children in a propensity score matched analysis. Variables used to generate propensity scores were: failure to thrive, congestive heart failure, preoperative LAVV regurgitation, associated congenital heart disease, sex and the presence of trisomy 21. Results: pAVSD repair was performed on 430 children, 17.4% (75/430) were infants. Infants (mean age 0.5±0.3 years) had higher rates of LAVV regurgitation, heart failure and additional cardiac malformations than older children (mean age 4.7±3.5 years). At 30 years, survival for infants was 82.1% (95% CI 70.1% to 89.6%) compared with 95.7% (95% CI 91.3% to 97.9%) in older children (P<0.001). Propensity score matching yielded 52 well-matched pairs. Survival at 30 years was 87.9% (95% CI 75.0% to 94.4%) for infants compared with 98.1% (95% CI 87.1% to 99.7%) for older children (P=0.04). There was no significant difference in freedom from reoperation between the groups. Conclusions: Despite matching for risk factors, survival after repair of pAVSD during infancy is lower than that when repair is performed in older children, with no difference in reoperation rates. This suggests that elective repair of pAVSD should be deferred until after infancy.